2016
DOI: 10.1371/journal.pone.0165787
|View full text |Cite
|
Sign up to set email alerts
|

Rifampicin-Induced Hepatic Lipid Accumulation: Association with Up-Regulation of Peroxisome Proliferator-Activated Receptor γ in Mouse Liver

Abstract: Previous study found that rifampicin caused intrahepatic cholestasis. This study investigated the effects of rifampicin on hepatic lipid metabolism. Mice were orally administered with rifampicin (200 mg/kg) daily for different periods. Results showed that serum TG level was progressively reduced after a short elevation. By contrast, hepatic TG content was markedly increased in rifampicin-treated mice. An obvious hepatic lipid accumulation, as determined by Oil Red O staining, was observed in mice treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 44 publications
4
21
1
Order By: Relevance
“…20 In the treatment regimen of tuberculosis, RIF is the first-line drug, but exerts sever hepatototoxicity after its administration. 21 The present study indicated that all the toxicity related marker enzymes like ALT, AST. ALP and LDH (Fig.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…20 In the treatment regimen of tuberculosis, RIF is the first-line drug, but exerts sever hepatototoxicity after its administration. 21 The present study indicated that all the toxicity related marker enzymes like ALT, AST. ALP and LDH (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…Previously, it was reported that RIF mediated liver damage is done by increasing oxidative stress in mitochondria, apoptotic response of liver cell, cholestasis effects, and hepatic lipid accumulation in rodent. 21 The accumulation of lipid in hepatic cells is made via upregulation of peroxisome proliferators activated receptor gamma (PPAR). Recently, Kim et al 9 had observed that upregulation of PPAR stimulates the expression of five proteins (apolipoprotein C-III, acyl-CoA-binding protein, 3-ketoacyl-CoA thiolase A and B, and perilipin-2) related to lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid accumulation is upregulated by PPARγ activation. Treatment with rifampicin (200 mg/kg) in mice for 4 weeks results in elevated hepatic lipids caused by induction of PPARγ through rifampicin-mediated activation of pregnane X receptor (PXR) [30]. A recent toxico-proteomics study suggests that the PPARγ signaling pathway is involved in rifampicin-induced liver injury [31].…”
Section: Specific Molecular Mechanisms Of Isoniazid/rifampicin-inducementioning
confidence: 99%
“…Our data points to the importance of the enzyme that produces 4b-HC, Cyp3A4 (Cyp3A11 in mice) (Bodin et al, 2001), as a crucial regulator of lipogenesis. Consistent with that, several groups have reported that increased Cyp3A4 expression by over expressing its activator, Pregnane X Receptor (PXR), correlated with increases lipogenic gene expression as well as liver triglyceride levels (Huang et al, 2016;Zhou et al, 2006). Conversely, decreased Cyp3A4 expression (He et al, 2013) or its pharmacological inhibition (Chudnovskiy et al, 2014) were associated with lower lipogenic gene expression and liver triglyceride levels.…”
Section: Discussionmentioning
confidence: 79%